What has been done to tackle overweight and obesity in Malaysia?: a literature review (2005 – 2015) - Tan, Siew Tin; Mohd Sidik, Sherina; Gyanchand Rampal, Lekhraj Rampal; Ibrahim, Normala; Tan, Kit Aun; Ibrahim, Zuriati (Universiti Putra Malaysia Press, 2017)
As reported by the World Health Organisation, Malaysia is the fattest country (Malaysian adults with the highest prevalence of overweight, body mass index equal or more than 25kg/m2) among the Southeast Asia. Among others, obesity is a leading contributor of non-communicable diseases (e.g., type II diabetes and cancer). This article aims to review the exiting weight management programmes targeting overweight and obese adults in Malaysia from 2005 to 2015. EMBASE, MEDLINE and PubMed were used to search for the published literature. Out of 544 articles, eight articles were selected for this review. Components of the intervention programmes in this review were: “spirituality-based programmes”, “dietary-based and physical activity programmes” and “diet, physical activity and behaviour modification-oriented programmes”. The findings from this review could be useful for future intervention efforts in an attempt to address such issues in Malaysia. Weight management or weight reduction intervention can be conducted among overweight or obese Malaysian adults in order to reduce the prevalence of overweight and obesity, therefore reduce the prevalence of non-communicable diseases in Malaysia.